“If I tell you I’m 13 online, will you believe me?”: implications for undercover internet stings - Drouin, Michelle; Egan, Vincent; Yergens, Nicholas; Hernandez, Elisa (American Psychological Society, 2018)
We examined the extent to which 262 adults, recruited from both a U.S. university sample and Amazon’s Mechanical Turk, believed the identity of a 13-year-old boy or girl persona in an online chat room. Sixteen undergraduate confederates (aged 19-38) followed two basic biographical sketches (Amber or James) and were instructed to “chat like a teenager” in one-to-one private chats. Confederates cycled through conditions where they provided no age or gender information (control), stated their age and gender, stated their age and gender and provided a picture (attractive or average), or stated their grade only. In all but the control condition, participants estimated the average age of their chat partner to be 13-14. Meanwhile, when confederates stated their age and gender, 83-88% of participants believed the confederate’s stated age, and 94-98% believed their gender. When asked about cues used to discern age and gender, most participants (98%) used multiple cues, including stated age and gender, content cues, style cues, and picture. Moreover, natural language analyses showed that the confederates used significantly fewer analytic words, fewer six-letter words, and displayed less clout than the adults with whom they chatted, and confederates who used more analytic words were perceived as older. Our findings contradict Lincoln and Coyle (2013) and suggest that even confederates who are not specially trained law enforcement agents are able to deceive others as to their age and gender in online chat rooms. These findings have important implications for those conducting undercover Internet stings and those who prosecute those cases.